The Efficacy of Appendicitis Inflammatory Response Score in Diagnosis of Acute Appendicitis (Sir Salimullah Medical College Journal, 2023)
Background: Acute appendicitis is one of the most common cause of acute abdominal pain. The management of suspected appendicitis represents a prime target for improved decision-making in emergency surgical care (OPD, Emergency room). The aim of the work is to evaluate the appendicitis inflammatory response (AIR) score and compare its performance in predicting the risk of appendicitis to the Alvarado score.Objective: To evaluate the diagnostic performance of the AIR score and potential benefits of risk stratification to guide clinical decision making.Methods: This prospective observational study was conducted in the OPD and Emergency department, Sir Salimullah Medical College & Mitford Hospital, Dhaka. From June’2021 to May’2022. A total 240 patients with right lower abdominal pain. History, clinical examination, hematological, radiological investigations were done. AIR score was calculated. Considering histopathology report as gold standard the score was compared. Histopathology report was done in Pathology Department of SSMC, Dhaka.Results: Right iliac fossa pain (100%) was the most common symptom, followed by vomiting (58.3%), temperature (29.5%), and rebound tenderness. After applying AIR scorings, 44(18.3%) patients in low-risk group (0-4), 112(46.7%) patients in the intermediate risk group (5-8) and 84(35.0%) patients in the high-risk category (9-12). Amongst the 240 applying the AIR score, Sensitivity of inflammatory response score vs histopathology findings was 97.9%, specificity 78.4%, accuracy 93.8%, positive and negative predictive values were 94.4% and 90.9% respectively.Conclusion: Risk stratification of patients with suspected appendicitis by the AIR score could guide decision-making to reduce admissions, length of hospital stay, cost and case fatality rate, optimize utility of diagnostic imaging and to decrease negative exploration.Sir Salimullah Med Coll J 2023; 31: 47-52